This is tricky.
First I'll introduce a Maclaurin series, then use it to sum your series.
The Maclaurin series for 2/(1 - (x/2)) is
2/(1 - (x/2)) = 2∑(x/2)^n,
where the sum is taken from n = 0 to ∞. I may rewrite this as
2/(1 - (x/2)) = 2∑(x^n)/(2^n).
Now take the derivative of both sides:
1/(1 - (x/2))^2 = 2∑(nx^(n - 1))/(2^n),
where the sum is taken from n = 0 to ∞. Now, on the right side, the n = 0 term will be zero, so I may rewrite this as
1/(1 - (x/2))^2 = 2∑(nx^(n - 1))/(2^n)
where the sum is taken from n = 1 to ∞ this time. Now, re-index the sum; start from n = 0 instead of n = 1 and replace all the n's inside the summation with n + 1. This gives
1/(1 - (x/2))^2 = 2∑(n + 1)x^n/(2^(n + 1))
where the sum is taken from n = 0 to ∞. Now bring the 2 that's out front on the inside, cancelling one of the 2's on the bottom on the inside:
1/(1 - (x/2))^2 = ∑(n + 1)x^n/(2^n)
where the sum is taken from n = 0 to ∞. Now plug in x = 1 (which is within the radius of convergence, 2):
1/(1 - 1/2)^2 = ∑(n + 1)/(2^n)
4 = ∑(n + 1)/(2^n).
Since this sum is taken from n = 0 to ∞, then to find your sum, we must subtract off the n = 0 term. The n = 0 term is 1; 4 - 1 = 3.
So your series sums to 3.
2007-04-09 23:00:32
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
I see someone else answered it with McLaurin series. That's the educated way. I forgot how to do that but I did it with what my first year profs called a Cheap Trick, and it's a lot more fun when it works!
first, your series can be written as sum(1 to inf) of n/2^n + sum(1 to inf) of 1/2^n. That's just rearranging the summands.
Now the series sum(1 to inf) 1/2^n famously equals 1. No need to go into detail about that.
Now all that's left is
sum(1 to inf) n/2^n
now for the CHEAP TRICK...
this series looks like
1/2 + 2/4 + 3/8 + 4/16 + 5/32 + 6/64 + ...
can be rearranged like:
= 1/2 + 1/4 + 1/8 + 1/16 + 1/32 + ...
+ 1/4 + 1/8 + 1/32 + 1/64 + ...
+ 1/8 + 1/16 + 1/32 + 1/64 + ...
+ 1/16 + 1/32 + 1/64 + ...
see how that rearranges each of the two fourths, and the "3/8", and the "4/16", etc?
the first line is the same series 1/2^n converging to 1; the second is the same, converging to 1 - 1/2, and so on.
now this sum equals
1
+ (1 - 1/2) ; <---this equals 1/2
+ (1 - 1/2 - 1/4) ;<--this equals 1/4
+ (1 - 1/2 - 1/4 - 1/8) ;<--catching on?
+ ...
= 1 + 1/2 + 1/4 + 1/8 + ...
= 1 + 1 = 2 shazzam!
so if sum(1 to inf) n/2^n = 2, then sum(1 to inf)(n + 1)/2^n = 2 + 1 = 3 shazzam!
I only say shazzam when I have solved something using a cheap trick.
btw I bet this is the simplest answer you get. cheap-trick answers usually are. It all keys off the basic convergent arithmetic series sum(1 to inf)1/2^n = 1, which you can practically prove in your head.
2007-04-09 23:55:39
·
answer #2
·
answered by kozzm0 7
·
0⤊
0⤋
Σ(n+1)/(2^n) = Σn/(2^n) + Σ1/(2^n)
This second series converges to 1. You can show that the first series converges to 2, to make a total sum of 3.
Let S[k] be the partial sum of Σn/(2^n) up to n=k. Then:
S[k] = Σ(n)/(2^n)
(1/2)S[k] = (1/2)Σ(n)/(2^n)
(1/2)S[k] = Σn/2^(n+1)
(1/2)S[k] = Σn=1-to-k n/2^(n+1)
(1/2)S[k] = Σn=2-to-k+1 (n-1)/2^n
(1/2)S[k] = Σn=2-to-k+1 [n/2^n] - Σn=2-to-k+1 [1/2^n]
(1/2)S[k] = Σn=2-to-k+1 [n/2^n] - Σn=1-to-k+1 [1/2^n] + 1/2
(1/2)S[k] = Σn=2-to-k+1 [n/2^n] - Σn=1-to-k [1/2^n] + 1/2 - 1/2^(k+1)
(1/2)S[k] = Σn=2-to-k+1 [n/2^n] - (1 - (1/2)^k) + 1/2 - 1/2^(k+1)
(1/2)S[k] = Σn=2-to-k+1 [n/2^n] - 1/2 + (1/2)^k - 1/2^(k+1)
(1/2)S[k] = Σn=2-to-k+1 [n/2^n] - 1/2 + (1/2)^k (1 - 1/2)
(1/2)S[k] = Σn=2-to-k+1 [n/2^n] - 1/2 + (1/2)^k (1/2)
(1/2)S[k] = Σn=2-to-k+1 [n/2^n] - 1/2 + (1/2)^(k+1)
(1/2)S[k] = Σn=1-to-k+1 [n/2^n] - 1/2 - 1/2 + (1/2)^(k+1)
(1/2)S[k] = Σn=1-to-k+1 [n/2^n] - 1 + (1/2)^(k+1)
(1/2)S[k] = Σn=1-to-k [n/2^n] + (k+1 /2^(k+1)) - 1 + (1/2)^(k+1)
(1/2)S[k] = S[k] + (k+1 /2^(k+1)) - 1 + (1/2)^(k+1)
-(1/2)S[k] = (k+1 / 2^(k+1)) - 1 + (1/2)^(k+1)
S[k] = -(k+1 / 2^k) + 2 + (1/2)^(k)
S[k] = 2 - (k/2^k)
Ugh, I think I messed up some where. But you can find the general proof of the Arithmetico-Geometric Series here:
http://mathforum.org/library/drmath/view/66996.html
2007-04-09 23:50:49
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
it would approach zero
proof01 : divide it by n the equation
gives ( 1+ 1/n ) / ( [2^n]/n )
as n approaches infinity 1/n ->0
also 2^n will grow much larger than n in the denominator
hence (1+0) / inf => 0
proof02: matlab program
2007-04-09 22:22:14
·
answer #4
·
answered by industrie 3
·
0⤊
1⤋
sum to infinity when a general term is given-
apply sigma to the term [n+1]/[2^n]
sigma n= n[n+1]/2
use this and simplify to get the answer
2007-04-09 23:30:53
·
answer #5
·
answered by Deranged Soul.. 2
·
0⤊
0⤋